2014
DOI: 10.1111/anu.12097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cholesterol levels on moulting performance, lipid accumulation, ecdysteroid concentration and immune enzymes activities of juvenile Chinese mitten crabEriocheir sinensis

Abstract: Effects of dietary cholesterol levels on moulting performance, lipid accumulation, ecdysteroid concentration and immune enzymes activities of juvenile Eriocheir sinensis were investigated. Crabs were fed with feeds contained various cholesterols of 1100, 2100 and 3200 mg kg À1 in both paddy fields and laboratory experiments. In paddy fields trial, the crabs fed with diets contained 3200 mg kg À1 cholesterol achieved higher growth rate than those fed with diets contained no supplemental cholesterol (1100 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
5
15
0
Order By: Relevance
“…This suggests that cholesterol supplementation improves the immune response of swimming crabs. Similar results were also observed in Eriocheir sinensis (Tao et al, 2014) and Oncorhynchus mykiss (Deng et al, 2013). However, the ACP and AKP levels of swimming crabs fed diet with 1.4% cholesterol were lower than those fed diets with 1.0% cholesterol.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests that cholesterol supplementation improves the immune response of swimming crabs. Similar results were also observed in Eriocheir sinensis (Tao et al, 2014) and Oncorhynchus mykiss (Deng et al, 2013). However, the ACP and AKP levels of swimming crabs fed diet with 1.4% cholesterol were lower than those fed diets with 1.0% cholesterol.…”
Section: Discussionsupporting
confidence: 82%
“…It is well known that crustaceans are incapable of de novo synthesis of sterols and require an exogenous dietary source of cholesterol for growth, development, and survival. Cholesterol is the ultimate precursor for the synthesis of ecdysone, which is closely involved in the process of molting in crustaceans (Sheen, 2000;Tao et al, 2014). Moreover, cholesterol is a precursor of vitamin D, which enhances the immune system (Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the total commercial production of Chinese mitten crab has reached at about 800,000 MT/year exceeding 5.5 billion USD in value (FAO ; Yuan, Wang, Zhang, Li, & Liu, ). Because of their high value, the species has been receiving significant attention to investigate various aspects of physiology and genetics (He et al., ), nutritional requirement (Pan, Xiao, Zhang, & Luan, ), digestible protein‐to‐energy ratio (DP:DE) (Cui et al., ; Li, Li, Liu, & Murphy, ), water temperature (Yuan et al., ) and the effects of various macro‐ and micronutrients such as phospholipid, cholesterol, vitamins and long‐chain fatty acids on production performance (Sui, Wille, Cheng, & Sorgeloos, ; Sun, Chen, Chen, Jiang, & Li, ; Sun et al., ; Tao et al., ; Wang et al., ; Wei et al., ; Wu et al., ). Recently, there is some focus on disease and immune enhancement of the species under farmed conditions (Ding et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying reasons for molt death syndrome are related to inadequate content of nutrients (e.g., high unsaturated fatty acids, PL, CH, and total lipids), which are stored in the hepatopancreas [11,[28][29][30]. Previous studies have shown that CH transported from the hepatopancreas results in the variation of the ecdysteroid signal transduction and changes the molting performance in crustacean [4,31,32].…”
Section: Introductionmentioning
confidence: 99%